LEGALITAS PENGGUNAAN GPS SELAMA BERKENDARA MELALUI SMARTPHONE PASCA PUTUSAN MK NO. 23/PUU-XVI/2018 - Nugraha, Xavier; Budianto, Anneta Cornelia; Hadiwidjayanti, Rizky (UNES Law Review, 2019)
Nowadays, using GPS as a navigator from smartphone is increasing, but it turns out there is a legal issue. This is related to the concept of driving with full concentration in Article 106 paragraph (1) of Law Number 22 Year 2009. In the explanation of Article 106 paragraph (1), there is an ambiguity in the interpretation between being able to use GPS, as long as it does not cause a concentration disturbance in driving or it is prohibited from using a cellphone at all, which means, using GPS via a smartphone is not allowed. This research is a study using normative law, with primary legal materials is legislation related to the use of GPS through smartphones during driving, such as, Law Number 22 Year 2009 concerning Road Traffic and Transportation and Constitutional Court Decision No. 23 / PUU-XVI / 2018, while materials Secondary law consists of books, journals, and other sources that are relevant. Based on the results of this study, it was found that the Constitutional Court provided an interpretation, that using GPS via a smartphone during driving was permitted, but it should not cause a concentration disturbance while driving and the application of such sanctions was casuistic. Keywords: GPS, smartphone, driving with full concentration,